ANALISA PENGARUH VARIASI ECHO TRAIN LENGTH (ETL) PADA SEKUEN T2 WEIGHTED IMAGE (T2WI) AXIAL PROPELLER TERHADAP KUALITAS CITRA PEMERIKSAAN BRAIN MAGNETIK RESONANCE IMAGING (MRI) - Dwi Kurniarahman, Yoyok; Santoso, Gunawan; Darmini, Darmini (JRI (Jurnal Radiografer Indonesia), 2020)
Backgroud: Echo Train Length (ETL) or turbo factor refers to the echo number of radiofrequency pulse refocusing 1800 after excitation RF pulse which used in Fast Spin Echo (FSE). ETL was is the single most important parameter on the image quality. Longer ETLs result in more T2-weighting because more late echoes with longer TE’s contribute to the overall signal. Longer ETL’s also associated with a decrease in the overall signal-to-noise ratio (SNR) and contrast-to-noise ratio (CNR) because the later echoes are weaker and the image having blurring. The ETL was influence with scanning time. PROPELLER sequences can be reducing the artefact motion. The aim of this research is to known how the effect of the ETLs variation on sequences T2WI axial PROPELLER to the best image quality and the ETLs value which have best quality. Methods: This type of study is a quantitative study conducted with an experimental approach in Radiology Installation of Santo Borromeo’s Bandung. Data is collected by the examination brain MRI in 6 (six) patients, after a brain MRI scanning with axial slice T2WI PROPELLER sequences, with variation of Echo Train Length (ETL). The variation of ETL we used are 12, 18, 24 and 30. And the estimation using Region of Interest (ROI) at the ventricle lateral, nucleus caudate, putamen, thalamus and internal capsule. The assessment results are summarized and then in a statistical test using SPSS version 23.0 with the method of Pearson correlate and linier regression. Results: The result showed that there is having effect of Echo Train Length (ETL) on sequences T2WI axial PROPELLER to the image quality. There is a strong correlation which the result of significant value 0,000 < p value 0.05. The relation effect variation of ETL with SNR very strong is nucleus caudate and CNR very strong between nucleus caudate and ventricle lateral. The mean rank value of SNR and CNR have been showed is ETL 12 with a mean rank up to 152,57 and 121,18 Conclusion:There was the influence of the echo train length toward image quality of brain MRI on sequences T2WI axial PROPELLER. The best echo train length value of brain MRI on sequence T2WI axial PROPELLER is 12.